Diversity of Gastropods and Bivalvia in Jukung Bay Waters, Pemongkong Village, Jerowaru District, East Lombok Regency - Ardiansyah Ardiansyah; Paryono Paryono; Saptono Waspodo (Jurnal Biologi Tropis, 2023)
Several activities affect the distribution of gastropods and bivalves, one of which is the activity of the community around the coast which is thought to affect water quality. The entry of organic and inorganic contaminants into coastal waters is thought to cause a decrease in water quality followed by changes in physics, chemistry and biology. The purpose of this study was to determine the diversity of gastropods and bivalves in the waters of Jukung Bay, Ujung Betok Hamlet, Pemongkong Village, Jerowaru District, East Lombok Regency. This research was conducted in Ujung Betok Hamlet (Tukung Bay Waters), Pemongkong Village, Jerowaru District, East Lombok Regency. the study was conducted from October 2022 to July 2023. The results showed that the highest species abundance was found in the Gastropoda class Nassarius sp with an abundance of 31 individuals/m2. The highest gastropod and bivalves diversity index value was obtained at point 3, namely 0.42 individuals/m2. The highest gastropod and bivalves uniformity index value was obtained at point 2 with a uniformity index value of 0.28. The dominance index value obtained was 0.1-0.56 individuals/m2 included in the moderate dominance category. Based on the results and discussion it is known that the abundance of gastropods and bivalves in the coastal waters of Jukung Bay which were analyzed totaled 108 individuals. The diversity index (H') obtained in this study ranged from 0.41-1.39 individuals/m2. The uniformity found ranged from 0.14 to 0.28 individuals/m2. The dominance index obtained ranged from 0.1 to 0.56 individuals/m2.